2023
DOI: 10.3390/su15021565
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Accident Risk Level Based on Construction Cost, Size and Facility Type

Abstract: Compared with other industries such as manufacturing, the construction industry has a higher danger of fatalities. In Korea, the risk level in the construction industry is managed using the fatality rate per 10,000 construction workers. However, this statistic is lacking in determining the exact risk level because it does not consider the exact number of workers and fails to reflect the specific characteristics of the construction industry. In this study, the fatality rate is deduced by considering the facilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…The results of this study have revealed several important findings compared to previous studies [5,9]. First, the proportion of fatal accidents in small-scale construction sites was found to be higher than that in medium-/large-scale construction sites.…”
Section: Discussionsupporting
confidence: 44%
See 3 more Smart Citations
“…The results of this study have revealed several important findings compared to previous studies [5,9]. First, the proportion of fatal accidents in small-scale construction sites was found to be higher than that in medium-/large-scale construction sites.…”
Section: Discussionsupporting
confidence: 44%
“…Similarly, Camino López et al [8] revealed that sites with fewer than 25 workers accounted for a staggering 58.1% of the total fatalities. Bang et al [9] analyzed fatality rates based on construction cost and facility type using accidents from 2013 to 2019. The study revealed that serious accidents frequently occurred at sites of less than 0.008 billion USD in South Korea.…”
Section: Accident Characteristics In Small-scale Construction Sitesmentioning
confidence: 99%
See 2 more Smart Citations
“…The prioritisation of health and safety indicators based on the SMART criteria and fuzzy TOPSIS approach can be used as a professional method of increasing awareness of construction safety and reducing risk levels. Risk-level-based evaluations based on facility type, size and construction cost are needed to estimate risk levels in the construction industry [108]. Based on the type of facility, the project size and the total cost, it was confirmed that the total fatality rate might exceed the fatality rate corresponding to each type of facility and the size of the project [108], and applying the suggested approach enables the determination of the quantitative risk level based on particular construction industry features.…”
Section: Ohsms Awareness and Model-related Analysismentioning
confidence: 99%